The Balloon Art Festival HOT AIR : Floating, Inflating, Touchable. - Ishikawa, Yoshinobu; Kitazawa, Hiromi; Matsui, Midori; McClean, Daniel; Nanjo, Fumio (Shizuoka : Executive Committee of the Opening Event of GRANSHIP, 1999)
Oiwa, Oscar Satio ; Murakami, Takashi ; Kusama Yayoi ; Lee, Bul ; Barney, Matthew ; Jeong-Hwa, Choi ; Nakamura, Tetsuya ; Fujiwara, Takahiro ; Dean, Tacita ; Navridis, Nikos ; Yoshimizu, Hiroshi ; Prix, The Balloon Art Grand ; Kasahara, Izuru ; Yamaide Jun'ya ; Warhol, Andy ; van Warmerdam, Marijke ; Wikstrüm, Elin ; Reinoso, Pablo ; Kaur, Permindar ; Reimer, Pierre ; Hemmert, Hans ; Shimano, Tsuneo
biografie
The Balloon Art Festival HOT AIR : Floating, Inflating, Touchable, Perfectural Convention & Arts Center - Granship, April 16 - April 25, 1999
Engels
boek